Magnetic Nickel iron Electroformed Trap (MagNET): a master/replica fabrication strategy for ultra-high throughput (>100 mL h−1) immunomagnetic sorting. Issue 16 (12th May 2016) - Ko, Jina; Yelleswarapu, Venkata; Singh, Anup; Shah, Nishal; Issadore, David
Abstract : We present a new approach to microfabricate micromagnetic sorting devices that can achieve highly specific cell separation at a throughput ( ϕ > 150 mL h −1 ) 100× greater than conventional microfluidics. Abstract : Microfluidic devices can sort immunomagnetically labeled cells with sensitivity and specificity much greater than that of conventional methods, primarily because the size of microfluidic channels and micro-scale magnets can be matched to that of individual cells. However, these small feature sizes come at the expense of limited throughput ( ϕ < 5 mL h −1 ) and susceptibility to clogging, which have hindered current microfluidic technology from processing relevant volumes of clinical samples, e.g. V > 10 mL whole blood. Here, we report a new approach to micromagnetic sorting that can achieve highly specific cell separation in unprocessed complex samples at a throughput ( ϕ > 100 mL h −1 ) 100× greater than that of conventional microfluidics. To achieve this goal, we have devised a new approach to micromagnetic sorting, the magnetic nickel iron electroformed trap (MagNET), which enables high flow rates by having millions of micromagnetic traps operate in parallel. Our design rotates the conventional microfluidic approach by 90° to form magnetic traps at the edges of pores instead of in channels, enabling millions of the magnetic traps to be incorporated into a centimeter sized device. Unlike previous work, where magnetic structures were defined using conventional microfabrication, we take inspiration from soft lithography and create a master from which many replica electroformed magnetic micropore devices can be economically manufactured. These free-standing 12 μm thick permalloy (Ni80 Fe20 ) films contain micropores of arbitrary shape and position, allowing the device to be tailored for maximal capture efficiency and throughput. We demonstrate MagNET's capabilities by fabricating devices with both circular and rectangular pores and use these devices to rapidly ( ϕ = 180 mL h −1 ) and specifically sort rare tumor cells from white blood cells.